Influence of silicone mammoplasty on the immunoendocrine status of female recipients - V. G. Zolotykh; A. N. Gvozdetsky; A. Ya. Kim; S. V. Lapin; L. R. Mikhailova; E. M. Starovoitova; T. V. Fedotkina; L. P. Churilov; Ye. Schoenfeld; P. K. Yablonsky (Медицинская иммунология)
The article concerns a study of early influence of silicone breast implants on the development of autoimmune reactions and dynamics of prolactin and thyroid hormone levels in women after mammoplasty. At the present time, this issue remains relevant for several reasons: more than 20 million pairs of implants have been installed in the world and the number of their implantations is constantly growing. Despite relative safety of the silicone implants, some of them are periodically banned by regulatory bodies in various countries. At the same time, there is a growing number of controversial publications in the scientific literature, about potential adverse consequences of their use. Some authors suggest an association between the silicone implants and risk of developing autoimmune conditions, connective tissue disorders, and occasional malignancies. On the other hand, the journals are full of publications about the overall safe tolerance of such medical devices by the patients. These considerations served as a pre-requisite to our research. As part of this project, we have assayed serum levels of autoantibodies to ten antigens, as well as contents of prolactin and thyroid hormones by means of ELISA technique in 27 patients before, 3 and 6 months after aesthetic and reconstructive mammoplastics performed within a period of September 2018 to November 2019. As a result, it was found that 5 out of 27 patients exhibited changes in the autoimmunity spectrum and intensity after mammoplasty. In particular, the concentrations of autoantibodies to modified citrullinated vimentin and IgM autoantibodies to cardiolipin exceeded the normal level at 3 and 6 months. In addition, the initially high prolactin concentration in mammoplasty recipients dropped to normal ranges by 3 months after breast surgery, even after several-fold increased initial levels. As for thyroid hormones, there were no statistically significant changes in their dynamics. The increase of autoantibodies to various target antigens after mammoplasty was statistically significant and positively correlated with each other. This can be explained, for example, by dependence on the adjuvant effect of silicone, which is not associated with antigen specificity. However, it may generally stimulate the immune responses.